OP0225 Mefv and TNFRSF1A Gene Mutations in Patients with Inflammatory Myopathy with Abundant Macrophages. (10th June 2014) - Fujikawa, K.; Migita, K.; Umeda, M.; Nonaka, F.; Kawashiri, S.-Y.; Iwamoto, N.; Ichinose, K.; Tamai, M.; Nakamura, H.; Mizokami, A.; Tsukada, T.; Origuchi, T.; et al.
Abstract : Background: Inflammatory myopathy with abundant macrophages (IMAM) is a new clinical condition characterized by diffuse infiltration of macrophages in fascia [1], but the mechanism remains unclear. Objectives: The objective of this study was to investigate the MEFV and TNFRSF1A mutations in patients with IMAM. Methods: Nine patients with IMAM were enrolled. Clinical characteristics, MRI, and pathologic findings were analyzed. Mutation analysis was performed by genomic sequencing of MEFV and TNFRSF1A. Results: The patients with IMAM had clinical symptoms such as myalgia, muscle weakness, erythema, fever, and arthralgia. STIR images in MRI showed thickening of fascia in all patients. In biopsied specimens from 8 patients, a number of CD68+ macrophages were found apparently in the fascia in all samples. In gene analysis, 7 of 9 patients had MEFV polymorphisms ( G304R, R202R, E148Q, E148Q-L110P, and P369S-R408Q ) and one patient had TNFRSF1A mutation ( C43R ). Conclusions: These results suggest that MEFV gene polymorphisms and TNRRSF1A mutations are susceptibility and modifier genes in IMAM. References: Bassez G, Authier F-J, Lechapt-Zalcman E et al. Inflammatory myopathy with abundant macrophages (IMAM): a condition sharing similarities with cytophagic histiocytic panniculitis and distinct from macrophagic myofasciitis. J Neuropathol Exp Neurol 2003; 62: 464-74. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1474